Nightmare in 3-D - Stine, R. L. (New York : Pocket Books, 1996)
Buying a 3-D poster at Sal's Five and Ten, Wes Parker spends several hours looking without success for the hidden image within the myriad of strange colors, but when he finally sees it, he wishes he had not.
"A Parachute Press book."
"A Minstrel book."
Accelerated Reader AR
Keywords: Science fiction; Optical illusions -- Fiction